Red blood cell transfusion does not increase risk of venous or arterial thrombosis during hospitalization. Issue 2 (16th November 2020) - Baumann Kreuziger, Lisa; Edgren, Gustaf; Hauser, Ronald George; Zaccaro, Daniel; Kiss, Joseph; Westlake, Matt; Brambilla, Donald; Mast, Alan E.; ,
Abstract: Previous observational studies suggest associations between red blood cell (RBC) transfusion and risk for arterial or venous thrombosis. We determined the association between thrombosis and RBC transfusion in hospitalized patients using the Recipient Database from the National Heart Lung and Blood Institute (NHLBI) Recipient Epidemiology and Donor Evaluation Study‐III. A thrombotic event was a hospitalization with an arterial or venous thrombosis ICD‐9 code and administration of a therapeutic anticoagulant or antiplatelet agent. Patients with history of thrombosis or a thrombosis within 24 hours of admission were excluded. A proportional hazards regression model with time‐dependent covariates was calculated. Estimates were adjusted for age, sex, hospital, smoking, medical comorbidities, and surgical procedures. Of 657 412 inpatient admissions, 67 176 (10.2%) received at least one RBC transfusion. Two percent (12927) of patients experienced a thrombosis. Of these, 2587 developed thrombosis after RBC transfusion. In unadjusted analyses, RBC transfusion was associated with an increased thrombosis risk [HR = 1.3 (95% CI 1.23‐1.36)]. After adjustment for surgical procedures, age, sex, hospital, and comorbidities, no association between RBC transfusion on risk of venous and arterial thrombosis was found [HR 1.0 (95% CI: 0.96‐1.05)]. Thus, RBC transfusion does not appear to be an important risk factor for thrombosis in most hospitalized patients.